Impact of Fairy Tales on the Development of Imagination Level of Preschool Children: Exploring the Influence of Fairy Tales on the Imagination Development of Pre Schoolers (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Fairy tales are crucial to the development of child's imagination. They show worldly common truths regarding men and the world around them in a simple manner. Tales and stories introduce the meaning of existence to the child, they show him aims pre-established by humans, teach proper behaviors, and what is more, familiarize children with moral norms rewarded by the society. Therefore, depicting the real world combined with fantastic phenomena in fairy tales compels the child to many reflections and conceptions. Fairy tale-inspired fantasizing gives children an ability to present the effects of their own creation by inventing new stories or transforming the already familiar literary works.